2018
DOI: 10.5350/dajpn2018310405
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the psychometric properties of the Turkish form of the Grief and Meaning Reconstruction Inventory

Abstract: Investigating the psychometric properties of the Turkish form of the Grief and Meaning Reconstruction InventoryObjective: The aim of this study is to adapt the Grief and Meaning Reconstruction Inventory (GMRI) to Turkish. Method: Three hundred and six adults who lost their spouse or one of their parents or siblings due to death in a period between 6 months and 10 years previously were included in the study. The participants were asked to complete a questionnaire set including GMRI, Beck Depression Inventory (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…According to Neimeyer (2006), if bereaved people can make sense of their loss, find something positive in it, and change their own identity according to new roles in life, their capacity for adaptation increases. In studies to date, meaning reconstruction has been found to have a negative relationship with prolonged grief symptoms (e.g., Gillies et al, 2015; Holland et al, 2006; Keser & Isikli, 2018). People who can make sense of the loss they experienced, see a positive side of the loss, and rearrange their identities might also use continuing bonds as a more adaptive coping mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Neimeyer (2006), if bereaved people can make sense of their loss, find something positive in it, and change their own identity according to new roles in life, their capacity for adaptation increases. In studies to date, meaning reconstruction has been found to have a negative relationship with prolonged grief symptoms (e.g., Gillies et al, 2015; Holland et al, 2006; Keser & Isikli, 2018). People who can make sense of the loss they experienced, see a positive side of the loss, and rearrange their identities might also use continuing bonds as a more adaptive coping mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The test–retest reliability values were found to be between 0.60 and 0.73. The GMRI was adapted to Turkish culture by Keser and Isikli (2018). Cronbach's α values of the Turkish form of the subscales were between 0.74 and 0.85 (Keser & Isikli, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that in order for a person to overcome the grieving process after a loss and reintegrate into the rhythm of daily life, it is necessary to reconstruct the collapsed world of meaning. 7 In addition to the grief experience, older adults often report a search for finding or reconstructing meaning in their lives after the death of a loved one. 8 In Neimeyer's constructivist approach, creating and reconstructing meaning after a death involves mourners reconciling with the loss, recognizing the growth or benefit that the experience of loss may have brought them, and reorganizing their personal identity.…”
Section: Introductionmentioning
confidence: 99%